The Convergence on a Family of Iterations with Cubic Order (Journal of Computational Mathematics, 2001)
In this paper, we establish a convergent theorem for a family of iterations with cubic order by using general convergence hypotheses. A sharp error estimate is also given explicitly.
Keywords: Convergence; Majorizing method; $γ$-Condition; Error estimate.